74 Nhse central midlands: gp international recruitment project. (31st October 2017) - Anwar, Mohammed Saqib; Rashid, Aly; Samanta, Ash
Abstract : NHS Central Midlands is leading a nationally approved pilot for recruitment of European GP's into Lincolnshire. This project was established by the Lincolnshire Local Medical Committee and supported by NHS England. Initial scoping throughout Europe revealed that one of the major barriers to recruitment of GP's from the EU to the NHS was the perceived poor pass rates for EU doctors in the I and R assessments and IELTS Language assessment, both of which are ordinarily required for GMC and Performers List registration as an entry point. This Project aimed to provide 25 fully qualified GP's into Lincolnshire. In this we developed a programme that helped mitigate some of these perceived barriers to entry, but retain the quality and standard of the doctors that were recruited. Eligible fully qualified GP's followed a 12 week residential intensive training programme including language, clinical and practical workshops at a campus in Poland. Language competency was assessed using The Common European Framework of Reference for Languages (CEF or CEFR). Successful completion allowed GP's to join the Performers List on a conditional basis, with the requirement to work at an approved practice under a named workplace supervisor who will provide monthly performance reports of the doctor. All doctors will do the I and R assessments at 6–9 months after arrival. The project has utilised innovative yet thorough ways to meet all of the regulatory requirements in respect of the GP's entry to the list, and NHS England hopes that with as a result of the education, training, support and conditions of inclusion we can support a safe and controlled introduction to UK NHS Practice for these doctors. It also hopes that by providing this controlled induction the chances of success at the I and R assessments are much greater. An independently commissioned evaluation of the entire project will follow but early feedback from the doctors, practices and patients is very encouraging indeed.